The Effects of Fish Oil on Cardiovascular Diseases: Systematical Evaluation and Recent Advance - Liao, Jia; Xiong, Qingsong; Yin, Yuehui; Ling, Zhiyu; Chen, Shaojie (Frontiers in Cardiovascular Medicine, 2022)
Fish oil is rich in unsaturated fatty acids, i.e., eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), both of which are widely distributed in the body such as heart and brain. In vivo and in vitro experiments showed that unsaturated fatty acids may have effects of anti-inflammation, anti-oxidation, protecting vascular endothelial cells, thrombosis inhibition, modifying autonomic nerve function, improving left ventricular remodeling, and regulating blood lipid. Given the relevance to public health, there has been increasing interest in the research of potential cardioprotective effects of fish oil. Accumulated evidence showed that fish oil supplementation may reduce the risk of cardiovascular events, and, in specific, it may have potential benefits in improving the prognosis of patients with hypertension, coronary heart disease, cardiac arrhythmias, or heart failure; however, some studies yielded inconsistent results. In this article, we performed an updated systematical review in order to provide a contemporary understanding with regard to the effects of fish oil on cardiovascular diseases.